Geoarchaeology - Geoarchaeology (Wiley, 2026)
Geoarchaeology is an interdisciplinary journal covering areas where archaeology and the geosciences collide. Our scope reaches beyond most journals, with a focus to understand archaeological sites, their formation, and their environment. Our mission is to understand the interrelationship between humans in the Quaternary period and their environment through geoarchaeological techniques and analysis of sedimentary records. We publish manuscripts examining archaeological questions within the Quaternary and Earth Sciences, because understanding our past helps our future.
FI 0.87
Q3
Keywords: Earth; Space & Environmental Sciences; Soil Science & Geoarchaeology; Edafología; Geoarqueología; Acuerdos transformativos; Transformative agreements; Climatología